PENERAPAN KOMPRES HANGAT DAUN KELOR DALAM MENGURANGI NYERI SENDI PADA LANSIA DENGAN ASAM URAT (GOUT ARTHRITIS) - Siska, Fera; Royani, Evi; Italia (LPPM STIKes Mitra Adiguna, 2025)
Gout often occurs in the elderly due to disorders of purine metabolism which causes pain in the joints. One non-pharmacological therapy that can be used to reduce pain is a warm compress from Moringa leaves, which contains flavonoids with anti-inflammatory and analgesic effects. This study aims to determine the effect of giving warm Moringa leaf compresses on reducing joint pain in elderly people with gout at the Harapan Kita Social Home, Palembang.. This research used a one group pretest-posttest design with a sample of 30 elderly people selected using a purposive sampling technique. Pain was measured before and after intervention using the Numeric Rating Scale (NRS). Data were analyzed using the Wilcoxon test. The average pain score before being given a warm Moringa leaf compress was 5.35 (moderate pain) and after the intervention it decreased to 3.54 (mild pain). The Wilcoxon test shows a value of p = 0.001 (p < 0.05), which means that there is a significant effect of giving warm Moringa leaf compresses on reducing pain. Giving warm compresses from Moringa leaves is effective in reducing joint pain in elderly people with gout. This therapy can be a simple and effective non-pharmacological alternative for treating pain.